A rare case of angiosarcoma presenting as pleuro-pulmonary metastasis: A case report - Abi G; Pugazhendhi S; Padamati Advytha; Nalini Jayanthi Nagesh (Asian Journal of Medical Sciences, 2025)
Angiosarcoma is an uncommon yet highly aggressive tumor originating from vascular endothelial cells, accounting for <2% of all sarcomas. Pulmonary involvement is often due to metastasis and presents with non-specific respiratory symptoms, leading to frequent misdiagnosis and delays in treatment. We report a case of a 74-year-old male with progressive breathlessness and recurrent hemoptysis. Imaging studies revealed multiple nodular deposits in the pleura and lung parenchyma. Histopathological and immunohistochemical analyses confirmed the diagnosis of metastatic angiosarcoma. This case underscores the significance of early recognition and histopathological confirmation in patients presenting with unexplained respiratory distress. A high index of suspicion is essential for timely diagnosis and intervention.